Knowledge Management and Green Commitment Analysis of Green Behavior Employee and Its Implication on Sustainability Corporate in Banking - Nawangsari, Lenny Christina; Sutawidjaya, Ahmad Hidayat; Maharini, Ade; Winata, Hendra (International Review of Management and Marketing, 2021)
This study aims to analyze the effect of knowledge management, green commitment and employee green behavior on organizational sustainability in banking institutions. The research method used is a qualitative method with the object of employee research at banking institutions in Indonesia. This study used a sample size of 150 people. Data analysis used SEM (Structural Equation Model) with PLS (Partial Least Square) software. The results of the study provide information about the influence of knowledge management, green commitment and green employee behavior on organizational sustainability in banking institutions. Keywords: Banking, Knowledge management, Green employee behavior, Organizational Sustainability JEL Classifications: G2, L2 DOI: https://doi.org/10.32479/irmm.10467